Exploring health policy development in Europe - Wood-Ritsatakis, Anne (WHO regional publications. European series, 2000)
Annotation Reports the results of a major study aimed at determining the extent to which health policy development in Europe has been guided by the principles, objectives, and targets of the WHO health for all frameworks. Noting that health for all is a value-driven policy, the study gives particular attention to the development of policy instruments that incorporate the principles of equity, participation, and intersectoral action. The study also aimed to measure the extent to which the health for all policy has operated as a successful tool for addressing health needs and reaching targets. Policy developments over the past two decades are considered for each of 50 European countries. The report has four chapters followed by a series of country profiles. Chapter one introduces the study and describes its goals, methodology, and sources of information. The second and most extensive chapter presents 13 in-depth case studies describing the health for all process in 10 European countries. Countries were selected as representing a range of different population needs, health priorities, systems for health care, and political and administrative structures. Each case study is presented according to a common framework that considers how the main principles of health for all have influenced the development of policies. Chapter three summarizes the results of this analysis, covering such topics as the criteria for setting priorities and targets, the extent to which the principles of health for all have been implemented, and the key question of whether successes in some countries can be duplicated in others. Chapter four extracts general lessons from these experiences, identifies shared problems, and considers the main challenges facing future health policy in Europe. These include growing inequities in health, social exclusion, demographic changes, rising expectations, and the globalization of economies and communication technologies. The report concludes with a series of 50 country profiles offering concise overviews of health for all policy development.